2003
DOI: 10.1088/0268-1242/19/2/021
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ge nanocrystals embedded in SiO2by Raman spectroscopy

Abstract: Ge nanocrystals formed in a SiO 2 matrix by ion implantation were studied by Raman spectroscopy. It is shown that Raman analysis based on the phonon confinement model yields a successful explanation of the peculiar characteristics resulting from the nanocrystals. A broadening and a shift in the Raman peak are expected to result from the reduced size of the crystals. Asymmetry in the peak is attributed to the variations in the size of the nanocrystals. These effects were observed experimentally for the Ge nanoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 22 publications
2
29
1
Order By: Relevance
“…A similar, though smaller, blue shift of Raman spectra of silicaembedded Ge nanocrystals is frequently observed and is attributed to matrix-induced compressive stress on embedded nanocrystals. [15][16][17][18][19][20] i. Quantitative Stress Analysis…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…A similar, though smaller, blue shift of Raman spectra of silicaembedded Ge nanocrystals is frequently observed and is attributed to matrix-induced compressive stress on embedded nanocrystals. [15][16][17][18][19][20] i. Quantitative Stress Analysis…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Among many properties of interest, structural information revealing crystal structure, nanocrystal shape, type and density defects is fundamental because they determine almost all other properties of the nanocrystals. Structural information can be obtained by several analytical techniques such as X-ray diffraction (XRD), transmission electron microscopy (TEM) and Raman scattering spectroscopy to name a few [2,3]. Ge nanocrystals have been obtained by ion beam synthesis in SiO 2 and post growth annealing [4,5].…”
mentioning
confidence: 99%
“…A presence of such a shoulder is then an indication of nano-sized structure. In our earlier publication, we showed that the size of Ge nanocrystals can be estimated from the asymmetric Ge peak [17]. The annealing temperature of 700°C is lower end of the temperature range in which Ge crystallization occurs.…”
Section: Resultsmentioning
confidence: 94%